Hubungan Tingkat Stres dengan Kejadian Hipertensi pada Lansia di Panti Sosial Tresna Werdha Natar - Fitri Julianti; Rika Yulendasari; Eka Yudha Chrisanto (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Introduction: Numerous reactions, including behavioral, emotional, cognitive, and physiological ones, are brought on by stress. The hormone adrenaline causes the arteries to tighten (vasoconstriction) and the heart rate to rise in response to stress, which raises blood pressure. Objective: At the Tresna Werdha Natar Social Home in South Lampung Regency, this study is to determine the association between stress levels and the prevalence of hypertension among the elderly in 2025.Method: This type of research uses a quantitative approach with a cross-sectional design. The population in this study is all elderly people in the Tresna Werdha Natar Social Home, South Lampung Regency in 2025 as respondents and stress levels are measured using a validated questionnaire while hypertension status is determined based on measurements. blood pressure according to WHO standards. In this study the sampling techniques used were total sampling and purposive sampling.Results: Based on the results of the study, it shows that out of 30 respondents who did not experience stress were 8 respondents (26.7%), and mild stress with 12 respondents (40.0%), moderate stress with 1 respondent (3.3%), and those who experienced severe stress were 6 respondents (20.0%). and some who experienced very severe stress with 3 respondents (10.0%).And respondents who experienced hypertension level 1 with a total of 18 respondents (60.0%), while hypertension level 2 amounted to 7 people (23.3%) and hypertension level 3 amounted to 5 respondents (16.7%). Stress levels and hypertension in the Tresna Werdha social home are significantly correlated, according to the statistical test results, which showed a p-value of 0.005 <0.05.Conclusion: The prevalence of hypertension among senior citizens at the Tresna Werdha communal home in 2025 is correlated with stress levels.Suggestion: It is hoped that it can increase knowledge about stress prevention, especially in the elder.